Dyskurs kształcenia digitalnego. Ontologia dyskursu kształcenia digitalnego i jego funkcje - Szczęsna, Ewa (Wydawnictwo Naukowe UAM, 2013)
The aim of the paper is to present the status of the learning discourse (especially forms of experimental use of educational text) in e-learning. Digital communication and digital tools (especially learner services, Internet, Web browsers) create a highly-effective and multi-dimensional learning environment. They modify the learning goals, methods and strategies, transform relationships between text and discourse, and between learning and teaching. They make education more flexible and intelligent. Digital technology used for the purpose of facilitating and supporting the educational process changes the status of the student and transforms the experience of multimedia training. It forces the student to become more creative, active and collaborative, commit himself to experiencing not only knowledge but also the learning discourse. It offers diversified and socially rich learning contexts.
The discourse of e-learning
Keywords: discourse; education; media; digitalization; e-learning